Теорія перекладу Богдана Лепкого та її практична реалізація в інтерпретаціях польською мовою поезій Тараса Шевченка - Васейко, Юлія; Vaseiko, Iuliia (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті представлений аналіз теорії тлумачення Б. Лепкого, описані засади інтерпретації лірики, запропоновані митцем, схарактеризовані способи їх практичної реалізації у перекладах віршів Т. Шевченка, виділені основні прийоми тлумачення, до яких вдається Б. Лепкий, окреслені причини лексичних трансформацій оригіналу. The analyze of B. Lepkyy’s interpretation theory was presented in this article, basic principles of lyrical poetries translations, that were offered by an artist, were described, the methods of their practical realization in translations of T. Shevchenko’s poems were determined, the basic ways of interpretation, that were used by B. Lepkyy, were selected, the most productive principles of translation were discovered, the reasons of lexical transformations in original were outlined. Analyze had improved that artist had used the basic rules of his interpretation theory in practice. His translation was successful because translator had understood poetry, had lived in it, had felt correctly and had reproduced main semantic and musical values of original artwork. B. Lepkyy’s interpretation was characterized by exactness, closeness to the original, adequacy in transmission of poetic semantic structure. Some differences in comparison with original text can be explained by author’s wish to represent the main themes, melodic, moods of T. Shevchenko’s artworks.
Bohdan Lepkyy’s theory of interpretation and its practical realization in Polish translations of T. Shevchenko’s poems
Keywords: художній переклад; оригінал; лірика; способи перекладу; лексичні трансформації; artistic translation; original; lyrical poetries; lexical transformations; methods of addition; replacement; admission; adequacy in translation; exactness in translation